Wearable Technologies - Nicola Carbonaro (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In the future, wearable technology will revolutionize the way we live. The current trend is to augment ordinary wearable objects - e.g. watches, glasses, bracelets, and clothing - with advanced information and communication technologies such as sensors, electronics, software, connectivity, and power sources. These wearable devices can monitor and assist the user in the management of his/her daily life with applications that range from activity tracking, sport and wellness, mobile games, and environmental monitoring, up to e-health. This book explores recent advances in the multidisciplinary field of wearable technologies and the important remaining gaps that must be addressed in order to obtain a massive diffusion. Articles in this book address topics that include wearable sensing and bio-sensing technologies, smart textiles, smart materials, wearable microsystems, low-power and embedded circuits for data acquisition, and processing and data transmission.